Application of drones in Indian agriculture - Abhishek Beriya (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2022)
Different prospects are offered by drones (small unmanned aerial vehicles) for the agricultural sector; typical drone applications being pesticide spraying, soil sampling and fertilizing, farm animal surveillance, real-time aerial imagery and sensor data collection etc. The Indian federal government is actively promoting drones for agriculture spraying. These 'Kisan drones' are primarily intended to cut down time, increase efficiency and efficacy of resource utilization in agriculture sprays (pesticides etc.) and mitigate adverse effects of manual pesticide spraying on human health. Going ahead, drones are also expected to help in transportation, surveying, and aerial imagery aspects in agriculture. This review finds that the government is actively pursuing a liberalised policy to promote drones and also offering substantial financial incentives to institutions, individual farmers as well as entrepreneurs to procure and use or manufacture drones as the case may be. Drones save time and are reported to be efficient in resource utilization with substantial water savings. Unit economics of drone spray cost per acre vis-à-vis manual labour cost is also catching up. Drone flying for agricultural operations can also be a good opportunity for rural youth. If drones are able to achieve confidence of farmers for spray related operations, there is a good chance their use can also be expanded to other advanced use cases, benefitting Indian agriculture.
Keywords: 330; Landwirtschaft; Agrartechnik; Drohne; Indien